Perfusion index as an early predictor of hypotension following spinal anesthesia for cesarean section - Roshana Prasad Mallawaarachchi; Vasanthi Pinto; P H D P De Silva (Wolters Kluwer Medknow Publications, 2020)
Introduction: Hypotension is a common complication after spinal anesthesia for cesarean delivery which is caused by sympathetic block 1. This can result in adverse maternal and fetal outcomes. Hence prevention and early treatment of spinal hypotension early has been a key research area in obstetric anesthesia. Intermittent non-invasive blood pressure measurement is the standard practice that fails to detect episodes of hypotension in a timely fashion. Methods: Noninvasive PI and blood pressure were measured in 109 healthy parturients undergoing elective cesarean section under spinal anesthesia. Results: PI appeared to increase significantly and more quickly in parturients with significant hypotension. Discussion: Findings may be due to the thoracic sympathetic blockade. Conclusion: Perfusion index can be a useful tool to early predict hypotension following spinal anesthesia for cesarean section. Response to ephedrine can be quickly assessed by the change in the PI which helps to decide on further boluses of ephedrine. Effect on the vascular tone by oxytocin is significant with 5IU bolus, though it does not cause a significant blood pressure drop.